Fertility of Bos indicus and Bos indicus X Bos taurus crossbred cattle after estrus synchronization - Tegegne, Azage; Warnick, A.C.; Mukasa-Mugerwa, E.; Ketema, H. (Elsevier, 1989)
Compares estrus response, estrus response interval and subsequent pregnancy rate in Bos indicus and Bos indicus X Bos taurus cross cows and heifers following estrus synchronization with prostaglandin F2 (PGF2X (a), a progesterone releasing intravaginal device (PR10) (b), and synchro-mate B (SMB) (c).